AN ANALYSIS SLANG WORD IN THE “FAST AND FURIOUS 7” MOVIE (Karya Ilmiah Mahasiswa (KIMA), 2023)
In this study the researchers focused on the slang words in fast furious 7 movie. The purpose of this study was “To find out what kinds and the meaning of slang word are used by main character in the fast and furious 7 movie”. The source of the data is obtained from the film script. The researchers design used in this study is descriptive qualitative. Qualitative methodlogy as a procedure that produces descriptive data in the form of written or oral words from people and observable behaviors. In this study the searchers was found two kind of slang word dan the meaning of the slang word have similar meaning in language general.